Premorbid factors of early post-stroke cognitive impairment - A. А. Grishina; A. M. Tynterova; Y. E. Skalin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The aim of this study is to identify and substantiate early cognitive dysfunction in patients with brain damage in the acute period of ischemic stroke.Materials and research methods. The study included 140 elderly patients. The main group included 70 patients of Vascular Surgery Center with a diagnosis of ischemic stroke in the carotid pool, the control group consisted of 70 outpatients. Cognitive function and psycho-emotional background were assessed using the Montreal Cognitive Function Scale, tests for kinetic, constructive and ideation praxis, the Stroop test, the Boston Naming Test, the apathy rating scale, the Hospital Anxiety and Depression Scale, and the MFI-20 asthenia scale. Assessment of neuroimaging parameters was carried out usingcomputed tomography. Assessment of long-latency acoustic endogenous evoked potential P300 using the «oddball active» paradigm technique was used for neurophysiological examination.Research results. Ischemic stroke was more often detected in the parietal, frontal lobes and basal ganglia. Moderate cognitive impairment was detected in 57.5% of patients with stroke and 27.5% of the control group. Dementia was diagnosed in 30% of patients in the main group and 5% of the control group. In patients with IS indicators characterizing the executive function, praxis, speech, attention, memory, depression, and apathy were statistically significantly lower comparing with the control group. The analysis of neurophysiological data revealed a statistically significant prolongation of the latency of the P300 wave in all leads and a decrease in the amplitude of the P300 peak in leads Cz and C3 in patients of the main group. Conclusion. Within the framework of this study, significant factors in the development of early post-stroke cognitive impairment were established. Dysfunction in attention, executive function, episodic memory, and speech is the result of a combination of causes directly related to cerebrovascular disease and pre-stroke factors. The evoked potential method reflects the degree of cognitive decline and can be used as a method for assessing the effectiveness of cognitive rehabilitation in stroke patients.